2016
DOI: 10.1128/aem.00376-16
|View full text |Cite|
|
Sign up to set email alerts
|

Vacuolar H+-ATPase Protects Saccharomyces cerevisiae Cells against Ethanol-Induced Oxidative and Cell Wall Stresses

Abstract: During fermentation, increased ethanol concentration is a major stress for yeast cells. Vacuolar H؉ -ATPase (V-ATPase), which plays an important role in the maintenance of intracellular pH homeostasis through vacuolar acidification, has been shown to be required for tolerance to straight-chain alcohols, including ethanol. Since ethanol is known to increase membrane permeability to protons, which then promotes intracellular acidification, it is possible that the V-ATPase is required for recovery from alcohol-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 50 publications
3
61
1
Order By: Relevance
“…In response to ethanol challenge, previous studies reported that yeast cells showed increased resistance to cell wall-lytic enzymes, which suggests adaptive remodeling of the yeast cell wall (3,6). We thus determined susceptibilities of wild-type cells to the cell wall-degrading enzyme Zymolyase, whose major activities are ␤-1,3-glucanase and ␤-1,3-glucan laminaripentaohydrolase, after treatment with ethanol or CFW.…”
Section: Resultsmentioning
confidence: 99%
“…In response to ethanol challenge, previous studies reported that yeast cells showed increased resistance to cell wall-lytic enzymes, which suggests adaptive remodeling of the yeast cell wall (3,6). We thus determined susceptibilities of wild-type cells to the cell wall-degrading enzyme Zymolyase, whose major activities are ␤-1,3-glucanase and ␤-1,3-glucan laminaripentaohydrolase, after treatment with ethanol or CFW.…”
Section: Resultsmentioning
confidence: 99%
“…Susceptibility to Zymolyase was examined as described previously (Charoenbhakdi et al 2016). Briefly, log-phase cells were diluted to an OD 600 of 0.5 in TE buffer [10 mM Tris–HCl and 1 mM EDTA (pH 7.5)] containing 100 mg L −1 (1 U) Zymolyase 20T (Zymo Research, Orange, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, expression of the autophagy genes ATG1 and ATG8 and the production of ROS under ethanol treatment in yeast were measured. The results showed that ethanol stress very significantly induced expression of the ATG1 and ATG8 genes and the production of hydrogen peroxide (H More and more studies showed that reactive oxygen species (ROS) were associated with fermentation [16][17][18][19]. ROS were a possible part of the yeast response to a variety of stress factors occurring during most fermentations [20].…”
Section: Introductionmentioning
confidence: 99%